SHADE: A MATLAB toolbox and graphical user interface for the empirical de-correlation of GRACE monthly solutions. (October 2018) - Piretzidis, Dimitrios; Sideris, Michael G.
Abstract: The Gravity Recovery and Climate Experiment (GRACE) mission provided monthly solutions of the Earth's gravitational field that are heavily influenced by noise. In this paper, we review the empirical de-correlation filter, designed for the post-processing removal of correlated errors in GRACE Level 2 data. We provide a detailed description of all filtering parameters along with their implementation strategies selected by previous studies. We present and discuss some aspects regarding the properties of the de-correlated GRACE data. We also design an integrated software, named SHADE (Spherical HArmonic coefficient empirical DE-correlation), for implementing the empirical de-correlation filter. SHADE is an open source software developed using MATLAB and consists of a toolbox and a graphical user interface (GUI). SHADE is designed to fully generalize the selection of filtering parameters. We test SHADE using one monthly solution of GRACE data and perform a comparison analysis using different sets of commonly used parameters. Highlights: We designed a software for the empirical de-correlation of monthly gravity data. The software generalizes the implementation of the empirical de-correlation filter. The software consists of a toolbox and a graphical user interface.